Meningkatkan Efisiensi Pengadaan Buku di Perpustakaan dengan Sistem Informasi Berbasis Komputer - Ariani, Linda; Hamdani; Alahuddin (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The development of a book procurement information system in libraries aims to replace inefficient manual methods with a more structured computer-based system. The designed system facilitates the recording of book data, suppliers, and procurement transactions, improving speed and accuracy in information management. A feasibility study was conducted to assess technical, operational, and financial readiness before system implementation. System analysis was carried out to identify existing challenges in the previous method, serving as the foundation for designing a new system with more optimal features. System design involves creating a normalized database to eliminate data duplication and enhance efficiency in information retrieval. System implementation includes testing and user training to ensure smooth adoption. Evaluation results indicate that this system accelerates the book procurement process, reduces recording errors, and simplifies transaction reporting. This research aligns with previous studies demonstrating that implementing a computer-based information system can enhance library service effectiveness. With a more integrated system, book management becomes more efficient, records are more accurate, and information is more accessible to users. Continuous development is expected to further adapt the system to library needs in addressing data management challenges in the digital era.